Acervo de escritores mineiros: gênese e constituição - Gustavo Lopes de Oliveira (2014)
The concern about the preservation of memory and historical construction of any nation involve power relations and the choices made about what to remember. Thus, the archive notion as heritage and memory comes up with the idea of national public property, which refers to the French Revolution. From this, this concern becomes also the thinking about ways and places to preserve national memory, and the function of the spaces that work with public archives, but also with private archives, including personal. Aiming to describe a historicalgenealogical path of the Acervo de Escritores Mineiros of the Faculdade de Letras of the Universidade Federal de Minas Gerais, there was a documentary analysis of the concepts of public archive and private archive and personal archive from a collective memory perspective. Through this process, it is noted that the idea of preservation in Brazil has been developed also from a notion that the personal archives of writers, politicians, and public people in general could, somehow, describe the nations history. This relates to the epistemological change that passed the various knowledge areas as literary studies, social sciences, information science, and in an increase of the national memory notion by which the subject takes its place in history. This vision guides the context of creating spaces as the one who is the object of this research. The ethnographic method used here also resulted in the association of classical archival science with a social archival science, through what was intended think the Acervo de Escritores Mineiros as a archive and experience it in order to understand its institutionalization.